Prediction of pathological complete response in breast cancer patients during neoadjuvant chemotherapy: Is shear wave elastography a useful tool in clinical routine?. Issue 128 (July 2020) - Maier, Anna Marie; Heil, Jörg; Harcos, Aba; Sinn, Hans-Peter; Rauch, Geraldine; Uhlmann, Lorenz; Gomez, Christina; Stieber, Anne; Funk, Annika; Barr, Richard G.; Hennigs, André; Riedel, Fabian; et al.
Highlights: Clinical trial of SWE during clinical routine for prediction of pCR in BC patients. SWE monitors reduced tumour stiffness during neoadjuvant chemotherapy in BC. pCR cases show higher reduction in shear wave velocity after only two NACT cycles. SWE shows improved sensitivity, high NPV, low FNR compared to standard assessment. SWE failed in specificity in order to predict pCR under routine conditions. Abstract: Objective: To compare the validity of Shear Wave Elastography (SWE) for the preoperative assessment of pathological complete response (pCR) to standard clinical assessment in breast cancer patients undergoing neoadjuvant chemotherapy (NACT). Materials and Methods: This prospective, consecutive clinical trial was conducted under routine clinical practice. Analysis included 134 patients. SWE served as index test, final pathology from surgical specimen as reference standard. PCR (ypT0) was defined as primary endpoint. Elasticity changes were compared for the pCR- vs. non-pCR group. To determine the validity of shear wave velocity (Vs ), ROC analyses and diagnostic accuracy parameters were calculated and compared to the final standard clinical assessment by physical examination, mammography and B-mode ultrasound (ycT + vs. ycT0). Results: Vs was significantly reduced in pCR and non-pCR groups during NACT (pCR: ΔVs (abs) = 3.90 m/s, p < 0.001; non-pCR: ΔVs (abs) = 3.10 m/s, p < 0.001). The pCR-group showed significant lower Vs for all control visits (t1, 2, END : p < 0.001). ROC analysis of Vs yielded moderate AUCs for the total population (t0 : 0.613, t1 : 0.745, t2 : 0.685, tEND : 0.718). Compared to standard clinical assessment, Vs (tEND ) (cut-off: ≤3.35 m/s) was superior in sensitivity (79.6 % vs. 54.5 %), NPV (86.4 % vs. 77.5 %), FNR (20.4 % vs. 45.5 %), inferior in specificity (58.6 % vs. 77.5 %), PPV (46.3 % vs. 54.5 %), FPR (41.4 % vs. 22.5 %). Conclusion: SWE measures significant differences in tumour elasticity changes in pCR vs. non-pCR cases. SWE shows improved sensitivity compared to standard clinical assessment, high NPV and low FNR, but failed in specificity in order to predict pCR under routine conditions.